The Radical Subject Of Mariam In Madrasah Al-Rawabi Li Al-Banat Movie - masruroh, Beti Arisatul; Wahyudi, Jarot (Universitas Muhammadiyah Gorontalo, 2024)
This research reveals a form of deviant behavior from the main character in the film Madrasah al-Rawabi Li al-Banat, Mariam. This behavior is considered a form of radical behavior carried out as a form or effort to liberate oneself from something that controls it. To achieve a free world, Mariam, who is a radical subject, goes through several phases of concepts that have been formulated by Slavoj Zizek in his theory, including the imaginary phase, symbolic phase and real phase. This type of research is a literature study with a content analysis method, while the techniques used in data collection are listening and recording techniques. Based on the results of the study, it was found that there were forms of radical behavior with the cyber crime model (internet crime) carried out by Mariam to Layan and her two friends as a form of revenge or self-liberation from the shackles of bullying that befell her.